Specificity of inducible nitric-oxide synthase inhibitors: prospects for their clinical therapy. - Liu Zhao-qian; Wildhirt Stephen M; Zhou Hong-hao (Acta Pharmacologica Sinica, 2016)
Nitric oxide (NO) is a ubiquitous, naturally occurring molecule found in a variety of cell types and organ systems. It is a double-edged sword, beneficial as a messenger or modulator and for immunology self-defense, but potentially toxic. The formation and signal function of nitric oxide are mainly modulated by nitric-oxide synthase (NOS). Up to the present, a number of diseases, including circulatory shock, atherosclerosis, cardiac allograft rejection, chronic inflammation, cardiac infarction, cancer and so on, have been demonstrated that their pathogenesis may be involved in the sustained production of large quantities of nitric oxide. Animal studies and human studies have shown that specific inhibitors of inducible nitric-oxide synthase may be useful in the therapy of a variety of diseases associated with induction of nitric-oxide synthase. In this review, we compare and contrast these inhibitors along with examples of their use in the studies of medicine.